Micro Business Financing System and Development of Credit Lines in Albania - Qarri, Albert; Dumi, Alba; Demo, Ervin (Mediterranean Journal of Social Sciences, 2012)
The capacity of public administration was weak; the system, stemming from a party focused environment, was highlypoliticized. Corruption was pervasive in every facet of the public sector. Citizens feared public administration and did not trust itto provide even the most basic services in a fair or impartial way. The financial collapse in 1997 was a watershed event inAlbania's transition from its communist past. It highlighted the problems of Albania's economic governance capacity and, from anadministrative standpoint, reaffirmed and highlighted the inefficacy of a public administration, unable to enforce its laws andregulations. As the public's confidence in Albanian1 institutions had been significantly eroded by the recent events, restoring thepublic's trust in the government became the main priority of the government. In order to achieve this objective the capacity of thepublic administration needed to be dramatically strengthened.2 The donors concurred with this assessment. IDA, starting withthe 1998 CAS, considered governance and institution building as one of the central planks of its intervention and identified theneed to adopt and implement reforms to build an accountable and transparent state as the most important challenge facing theGovernment of Albania. Over the next several years, the Albanian Government, in partnership with donors, emphasizedinstitutional reform and capacity building and developed a comprehensive strategy to strengthen the public institutions for moreeffective governance.